Structural Investigation of Some Cr(III), Fe(III) and Co(III) Biligand Complexes - K. Agarwal, Suresh; Lal, Manohar (Asian Journal of Chemistry, 2010)
The biligand complexes of Cr(III), Fe(III) and Co(III) with 1-(o-methoxy anilinomethyl)-benzimidazole (MAB) as primary and 2-thio-pyrogallol (TP) or thiosalicylic acid (TSA) as co-ligand have been isolated and characterized on the basis of analytical, conductance, magnetic moment and spectral data. Their conductance data show that Cr(III) complexes are 1:2 electrolytes while Fe(III) and Co(III) complexes are non-electrolytes. IR Spectra reveal that both the ligands possess two donor sites in the complexes under study. On the basis of reflectance spectral and magnetic moment data octahedral configuration is assigned for these complexes.